Screening of Brinjal Varieties for Resistance Against Blight Disease Caused by Alternaria alternata (Fr.) Keissler in Konkan Region of Maharashtra, India - Phondekar, U.R.; Kadam, J.J.; Sanap, P.B.; Joshi, M.S.; More, V.G.; Potphode, P.D.; Pawar, H.D. (Archives of Current Research International, 2025)
Brinjal (Solanum melongena L.) belonging to family solanaceae, is widely recognized around the globe as “eggplant” due to it’s resemblance to the shape of a chicken egg. The field experiment was carried out during Rabi, 2022-23 and 2023-24 at Central Experiment Station, Wakawali, Dr. Balasaheb sawant Konkan Krishi Vidyapeeth, Dapoli under natural epiphytotic conditions. Sixty six varieties / cultivars and germplasm lines of brinjal were screened to test their resistance reactions against blight disease of brinjal caused by Alternaria alternata. The results revealed that, all the entries of brinjal screened showed varied degree of per cent disease intensity. The highest per cent disease intensity was recorded in Konkan Prabha (41.92%) and was followed by NB-746 (37.91%), Dapoli local-1 (34.62%) and Dapoli local-3 (33.42%). Among 66 entries screened, three entries viz., D-79-19, RCMB-3 and Dapoli pandharivangi sel. were found highly resistant, seven entries viz., Khed local-41, DPL-BR-19, NBH-106, Suwarna Pratibha, DPL-BR-20, N-1007 and NBH-104 resistant, thirty eight entries moderately resistant and eighteen entries of brinjal were moderately susceptible to A. alternata incitant of brinjal blight disease.